Model Manajemen Risiko Bencana Berbasis Komunitas Melalui Uji Publik Rencana Kontinjensi Erupsi Gunung Sinabung Kabupaten Karo - Puji Lestari; Eko Teguh Paripurno; Arif Rianto Budi Nugroho (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
The research aims to create a community-based disaster risk management (PRBBK) model through the Mount Sinabung eruption contingency plan program. This research uses qualitative descriptive methods. Data collection methods using table top exercise and field test exercise. Data analysis techniques used are data collection, data reduction, data presentation and withdrawal of conclusions at pre-research, during research, and post-research. The results showed that with the implementation of the field, it can improve the safety and preparedness of Karo district communities in the face of the disaster eruption Mount Sinabung. The contribution of this research is a model of community-based disaster risk management through the program of Mount Sinabung eruption contingency plan which is being processed into the regulation of the Karo District, North Sumatera.